2012
DOI: 10.1208/s12249-012-9908-y
|View full text |Cite
|
Sign up to set email alerts
|

Nanolipidgel for Enhanced Skin Deposition and Improved Antifungal Activity

Abstract: Abstract. The purpose of the research was to prepare and evaluate a topical nanolipidgel (NLH) of terbinafine hydrochloride (TRB), an antimycotic agent, for enhanced skin deposition and improved antifungal activity. Topical solid lipid nanoparticles (SLN) based nanolipidgel was formulated and evaluated. TRB-loaded SLNs were formulated by high-pressure homogenization technique. The stable TRB SLN dispersion was incorporated into a gel using 1% Carbopol 980 NF. Rheological evaluation and texture analysis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 34 publications
2
25
0
1
Order By: Relevance
“…Similar studies also reported that droplets moved more slowly from the inner phase to the outer phase in CG than in NG, probably because the droplets were larger in CG. 33,34 Ter and cIT accumulation in the sc and epidermis/dermis…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Similar studies also reported that droplets moved more slowly from the inner phase to the outer phase in CG than in NG, probably because the droplets were larger in CG. 33,34 Ter and cIT accumulation in the sc and epidermis/dermis…”
Section: Figurementioning
confidence: 99%
“…33,34 Moreover, differences in fluorescence signals among the NGs showed that the proportion of CP934 influenced the skin permeation rates by altering the main skin permeation routes. There are three major routes for drug penetration into the subepidermal tissue: hair follicles together with their sebaceous glands, sweat ducts, and the SC (including transcellular and intercellular routes).…”
Section: Figurementioning
confidence: 99%
“…The sample was placed between the gap of the cone and plate, and the gap was closed gradually. 37 Then the sample was subjected to a dynamic shear rate ranging from 7.5 to 45 S −1 (1-6 rpm) where shear stress and viscosity were measured. All the measurements were performed at isothermal condition at room temperature (25°C±2°C).…”
Section: Viscosity Measurementmentioning
confidence: 99%
“…Female Swiss albino mice of 20-25 g were selected for these studies. The negative control group was treated with normal saline 45 while formalin was used as a standard irritant 20,37 for the positive control group. The dorsal region of mice was shaved 24 h prior to the application of the formulations 52 using a hair remover cream (Veet ® , Reckitt Benchiser).…”
Section: Skin Sensitivity and Histological Examination Studiesmentioning
confidence: 99%
See 1 more Smart Citation